Redefinition of the genus Allonychiurus Yoshii, 1995 (Collembola, Onychiuridae) with description of a new species from China - Xin Sun; Jian-Xiu Chen; Louis Deharveng (ZooKeys, 2011)
In this paper, we describe a new species of the genus Allonychiurus Yoshii, 1995, characterized by the presence of an apical swelling on the fourth antennal segment as well as a combination of chaetotaxic and pseudocellar characters. The genus Allonychiurus is redefined. Four of its species are considered as incertae sedis: A. michelbacheri (Bagnall, 1948), A. spinosus (Bagnall, 1949), A. caprariae (Dallai, 1969) and A. sensitivus (Handschin, 1928). The three species A. borensis (Beruete, Arbea & Jordana, 1994), A. sensilatus (Thibaud & Massoud, 1979) and A. vandeli (Cassagnau, 1960) are removed from Allonychiurus and placed in Micronychiurus Bagnall, 1949, Thalassaphorura Bagnall, 1949 and Spinonychiurus Weiner, 1996 respectively. The synonymy of Thibaudichiurus Weiner, 1996 with Allonychiurus is rejected and A. foliatus (Rusek, 1967) and A. mariangeae (Thibaud & Lee, 1994) are re-allocated to Thibaudichiurus. List and identification key to the world species of the genus are given.